Pola Pengembangan Karakter Religius Aspek Ibadah dan Akhlak pada Siswa di SMPIT Rabbi Radhiyya Rejang Lebong - Tri Lestari; Sutarto Sutarto; Syahrial Dedi (At-Ta'lim : Media Informasi Pendidikan Islam, 2020)
Abstract: Pattern of Religious Character Development Aspects of Worship in Students at SMP IT Rabbi Radhiyya Rejang Lebong.This study aims to explore patterns of religious character development in aspects of worship and morals in SMP IT Rabbi Radhiyya Rejang Lebong students. This research is qualitative research with a phenomenological approach. Technique data obtained from interviews and observations. The data obtained were analyzed by four steps, namely data, data reduction, data presentation, leveraging, or pulling. The results showed that the development of religious character in the aspect of worship is carried out through obligatory prayers and sunnah (dhuha, rawatib) and tahfidz Qur'an. Development of religious character in the moral aspects including morals for teachers, morals towards others, and morals towards oneself. The development of religious character is carried out through a pattern of habituation, giving advice, guidance, control, and supervision, guidance, reward, and punishment, which includes knowledge, feelings, and actions.